2008
DOI: 10.1364/oe.16.018067
|View full text |Cite
|
Sign up to set email alerts
|

Photon emission by nanocavity-enhanced quantum anti-Zeno effect in solid-state cavity quantum-electrodynamics

Abstract: Solid-state cavity quantum-electrodynamics (QED) has great potential owing to advances such as coupled systems combining a nanocavity and a quantum dot (QD). These systems involve two photon-emission mechanisms: the Purcell effect in the weak coupling regime and vacuum Rabi-splitting in the strong coupling regime. In this paper, we describe a third emission mechanism based on the quantum anti-Zeno effect (AZE) induced by the pure-dephasing in a QD. This is significantly enhanced by the inherent characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 24 publications
5
76
1
1
Order By: Relevance
“…This certainly confirms that pronounced Purcell effects can be realized. A related theory of the spectral observations and second-order quantum correlation measurements are presented elsewhere [56,61] (see also [62][63][64]), which in general show the need for a medium-dependent theory, namely a theory that is based on quantizing the medium-dependent macroscopic electric field operators; using such a quantization procedure, the relationship between the electric field operators and the exciton operators is established directly with the mediumbased Green functions; this helps to clarify the underlying physics of photon emission processes in these chip-based structures, since unexpected observations can occur such as off-resonance excitation of the cavity mode [50,56].…”
Section: (2 C= 0 )mentioning
confidence: 99%
“…This certainly confirms that pronounced Purcell effects can be realized. A related theory of the spectral observations and second-order quantum correlation measurements are presented elsewhere [56,61] (see also [62][63][64]), which in general show the need for a medium-dependent theory, namely a theory that is based on quantizing the medium-dependent macroscopic electric field operators; using such a quantization procedure, the relationship between the electric field operators and the exciton operators is established directly with the mediumbased Green functions; this helps to clarify the underlying physics of photon emission processes in these chip-based structures, since unexpected observations can occur such as off-resonance excitation of the cavity mode [50,56].…”
Section: (2 C= 0 )mentioning
confidence: 99%
“…In contrast, in this Letter we investigate the resonant excitation of an InAs quantum dot that is strongly coupled to a photonic crystal cavity. We show that the resonantly excited QD emits efficiently through the cavity mode and model the interaction by a phonon-mediated dephasing model [5][6][7]. In this experiment, the cavity signal effectively becomes a spectrally separated readout channel for high-resolution single quantum dot spectroscopy.…”
mentioning
confidence: 91%
“…It has previously been reported that quantum dots that were pumped through higher excited states or the QD wetting layer can drive the cavity even when it is far detuned [2][3][4]. Several recent theoretical models attribute the off-resonant driving of the cavity mode to a pure dephasing mechanism of the quantum dot [5][6][7]. We describe our experimental data with a pure dephasing rate à [19].…”
mentioning
confidence: 97%
“…Third, direct spontaneous emission from the two-level system to free space is strongly suppressed due to the in-plane photonic band-gap effect in the case of the two-dimensional PhC nanocavities shown in Fig. 4(c) [84][85][86]. These features are well described by a factor F, which is given by where 2Γspon is the direct spontaneous emission rate of the TLS to free space, 2Γc is the damping rate of the cavity, which is determined by its Q factor, 2γphase is the pure dephasing rate of the TLS, δωTLS,c is the detuning of the TLS from the cavity, and g TLS,c is the coupling constant between the TLS and the cavity.…”
Section: Figmentioning
confidence: 99%
“…Recently, such a coupled system consisting of a nanocavity and a QD shown in Fig. 4(c) has been further extensively investigated because of its promising applications such as quantum information processing [4,[83][84][85][86], single photon sources [1,81,85], and ultimately low-threshold nanolasers [78,80,[86][87][88][89]. For such a single QD PhC nanocavity system, utilization of a single mode cavity with a sufficiently high Q factor as a lasing mode, the modal volume of which should be as small as possible to maximize the interaction with the single QD gain medium, is key to realize a thresholdless QD nanolaser.…”
Section: Figmentioning
confidence: 99%